University Student Perceptions of Technology Use in Mathematics Learning - Zogheib, Bashar (2015)
Although most universities and educators are relying on implementing various technological tools in the curriculum, acceptance of such tools among students is still not sufficient. The Technology Acceptance Model (TAM) has been widely used by researchers to test user’s acceptance of technology in business, education and other domains. This research study is an attempt that tests the integration of TAM and user satisfaction in the educational field. It particularly investigates students’ acceptance to use MyMathLab, a technological tool, in university math classes in the Middle East. Structural equation modelling with various constructs was used. Findings support the theoretical model showing the great influence of user satisfaction on perceived ease of use and subjective norm on behavioural intention. The findings of this study also demonstrate that selfefficacy, user satisfaction, subjective norms, perceived usefulness, perceived ease of use, and students’ attitude constructs all have a positive impact on students’ behavioural intentions to adopt and use technological tools in a mathematics class room. Findings of this research have greater implications for educators and students worldwide.